Detection Of Adulterated Non-Halal Fat (Lard) In Animal Fats Using Gc-Fid,Hplc,Dsc And Ftir Spectroscopy Evaluated With Chemometric Techniques - Dahimi Omar
The presence of lard or its derivatives in food products is a serious religious matter of concern in religions like Islam and Judaism.This raises the issue of food safety risk among worshipers of religions prohibiting the consumption of pork-derived products with extensions on the trade of commodities as well as ensuing legal concern. the physicochemical properties of lard ,makes it difficult to differentiate from other animal fats such as beef tallow and chicken fat. The objectives of this study were:(1) to monitor fatty acids (FA), and triacylglycerols (TAG)profiles of lard ,beef tallow ,and chicken fat using four different tools (GC,HPLC,DSC,and FTIR), (2) To characterize and detect concentration of lard of certain percentages, within different fats such beef tallow and chicken fat using the above-mentioned equipments and then analyzed with chemometric techniques ;and (3)To determine the lowest possible limit of detection of lard in animal fat mixture models for each instrument . Measurements were made on the extracted pure lard ,beef tallow ,chicken fat,and beef tallow (BT)and chicken fat (CF),mixed with LD in six different combinations (99.5% + 0.5% LD , 99% +1% LD,98% +2% LD,97% +3% LD,96% +4% LD,95% +5% LD).Sample were there after analyzed by GC-FID ,HPLC, DSC ,and FTIR.Data were standardized ,normalized,and mean centered before running principal component analysis (PCA) using the Unscrambler software for each data set.The scores and loading plots of each scaled data were studiedand compared .The GC-FID result showed that lard contained high C18:2 cis fatty acid (FA)and less C16:0 fatty acid (FA)as compared to beef tallow and chicken fat which scored 0.60% and 0.14% C18: 2cis and 56% and 71% C16:0 .respectively. The amount of C4:0 ,C14:0,and C18:0 FAs were approximately similar for all fats while those from HPLC analysis showed that lard contained higher PPL and PPO , and lower PLO triacylglycerols (TAGs) as compared to beef tallow .chicken fat showed similar features with lard .meanwhile ,the amount of OOP and PPP was roughly similar for all fats .Moreover ,DSC result showed that it could be employed to differentiate lard from beef tallow and chicken fat based on their onset temperature ,enthalpy,and end set temperature of cooling and melting thermograms .It was found that by using melting thermograms ,adulteration could be detected in beef tallow and chicken fat at concentration even less than 1% but this would be difficult to archive by using cooling thermograms especially in chicken fat mixed with lard. Chemometric techniques performed from PCA result were able to clearly differentiate lard ,beef fat ,chicken fat and the mixtures of lard and beef tallow ,lard and chicken fat at lower concentrated level (0.5% lard-99.5% beef tallow / chicken fat (w/w).However ,K-mean cluster was only able to classify and differentiate between the pure lard (LD), pure chicken fat (CF) and pure beef tallow (BT); but it was not able to differentiate pure beef tallow againts the treatment of beef tallow -lard mixture (<5 %lard) ;and pure chicken fat against chicken fat -lard mixture (<5%lard)